Antiviral therapy of COVID-19 - Janković, Slobodan M (Scripta Medica, 2020)
The COVID-19 pandemic required rapid response to the needs of critically ill patients, and one of the solutions was re-purposing of drugs with wide spectrum of antiviral action for treatment of the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) infection. The re-purposing characteristically started with outof-label use in single or series of cases, to continue after the first promising results with randomised clinical trials. There are several drugs that are currently tested in ongoing clinical trials: antimalarials hydroxychloroquine and chloroquine, HIV protease inhibitors lopinavir/ritonavir, broad spectrum antivirals umifenovir (anti-influenza drug) and favipiravir, antiparasitary drug ivermectin and nucleotide analogue remdesivir. However, up to date only a few trials are completed and published, precluding definitive conclusions about efficacy and safety of these drugs. Until major clinical trials are completed, physicians who decide to use these drugs out-of-label should properly inform their patients of all potential risks and benefits and seek for their consent before administration of the drugs.
Keywords: COVID-19; Antiviral agents; Drug repurposing; Out-of-label use; Adverse effects